PAPER EVALUATION GUIDE - Cox, Gerry (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Death education in sociology should provide students with an opportunity to gain a more scholarly understanding of the social processes involved in dying and death. The sociology of dying and death can analyze the processes and institutional responses to dying and death in the same way that it analyzes cities, crime, race, ethnicity, gender, sexuality, religion or any other sociological subject Like much in sociology, the possible approaches and topics are seemingly endless. Within this manual a number of possible approaches, taken from a number of different disciplinary perspectives, are provided for you to draw upon. The first section of the manual offers two helpful guides, including an historical overview of death education. Section II provides some examples of the many possibilities for organizing your course and the course content. In Section III, our attention is drawn to specialized topics in death education. Suggestions and examples of such projects, then, are included in Section IV. The final section of the manual is a reference for potentially useful resources.